2015
DOI: 10.18673/gs.v6i4.22100
|View full text |Cite
|
Sign up to set email alerts
|

Critérios para decisões sobre incorporação de tecnologias em saúde no Brasil e no mundo

Abstract: Com os crescentes gastos em saúde, muitos países estão adotando a ferramenta de Avaliação de Tecnologias em Saúde (ATS) para auxiliar as suas decisões sobre introdução de novas tecnologias nos sistemas de saúde. No Brasil, a Comissão Nacional de Incorporação de Tecnologias no SUS (CONITEC) é responsável por assessorar o Ministério da Saúde em suas atribuições relacionadas à incorporação, à exclusão ou à alteração de tecnologias em saúde pelo SUS. Com o objetivo de aprimorar o trabalho da CONITEC, foi realizada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…An examination of 12 reports drafted by Conitec showed that in the same way for the evaluated countries, information on effectiveness, safety, and cost-effectiveness were considered relevant in the process of the incorporation of technologies by the Committee 34 . It is worth mentioning, however, that Conitec reports were selected by convenience samples.…”
Section: Discussionmentioning
confidence: 99%
“…An examination of 12 reports drafted by Conitec showed that in the same way for the evaluated countries, information on effectiveness, safety, and cost-effectiveness were considered relevant in the process of the incorporation of technologies by the Committee 34 . It is worth mentioning, however, that Conitec reports were selected by convenience samples.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 15 studies offered a comprehensive assessment of HTA in Brazil. Specifically, two studies were based on surveys with Brazilian experts about the HTA implementation in Brazil [19,31], five studies were opinion pieces presenting a critical appraisal on the current HTA institutions in Brazil [8,10,24,25,36], seven were reviews of the Brazilian HTA reports [15,16,18,20,26,27,38], and one study was a literature review addressing the use of real-world data on Latin America [22].…”
Section: Development Of the Questionnairementioning
confidence: 99%
“…The judiciary and health associations accounted for only 4.3% (7) of the requesting parties during the period studied. Efforts are being made to increase the number of requests from entities linked to the SUS (Ministry of Health programs, state and municipal health departments) without affecting the application process, criteria and transparency of the reviews carried out by CONITEC and maintaining working standards that are comparable to international standards 31 .…”
Section: The Technology Assessment Agenda and Diseases Of Povertymentioning
confidence: 99%